In Vitro Vitamin K3 Effect on Conjunctival Fibroblast Migration and Proliferation. (8th January 2014) - Pinilla, I.; Izaguirre, L. B.; Gonzalvo, F. J.; Piazuelo, E.; Garcia-Gonzalez, M. A.; Sanchez-Cano, A. I.; Sopeña, F.
Abstract : Purpose . To evaluate the dose effect of vitamin K3 on wound healing mechanisms. Methods . Conjunctival fibroblasts were incubated for 24 hours. An artificial wound was made and the cells were incubated with fresh medium plus doses of vitamin K3 to be tested. Wound repair was monitored at 0, 18, 24, and 48 hours. Proliferation was measured in actively dividing cells by [ 3 H]thymidine uptake. Six different groups were tested: group 1/no drugs added, group 2/ethanol 0.1%, group 3/vitamin K3 1 mg/L, group 4/vitamin K3 2 mg/L, group 5/vitamin K3 4 mg/L, and group 6/vitamin K3 6 mg/L. Each experiment was carried out in triplicate and 4 times. Results . There were no differences among groups at the initial time. In vitro wound repair was slower in groups 4, 5, and 6. There were no differences between control and ethanol groups and between control and vitamin K3 1 mg/L groups. Fibroblast mitogenic activity was statistically decreased in all vitamin K groups; statistical differences were found among vitamin K3 1 mg/mL and higher doses too. In groups 5 and 6, cellular toxicity was presented. Conclusions . Vitamin K3 is able to inhibit fibroblast proliferation. Vitamin K3 2 mg/L or higher doses inhibit wound healing repair, exhibiting cellular toxicity at 4 and 6 mg/L.